The quality of the white pickled cheese in konva region - Saliha Altın; O Cenap Tekinşen (Eurasian Journal of Veterinary Sciences)
This investigation was carried out to determine the quality of white pickled cheese produced and consumed in Konya. Samples ol ten different companies were obtained from some retail markets. Fatty types cheese samples were randomly collected three times by monthly intervals. The average colony forming unit of aerobic mesophilic microorganisms, coliform bacteria. Staphylococcus spp.. Lactobacillus spp.. yeast and mould were determined as 1.60 x 1O0 clu/g, 1.75 x 10s cfu/ g, 1.69 x 103 cfu/g, 2.68 x 107 cfu/ g and 2.46 x 105 cfu/ g respectively. The average values moisture . dry matter, lat in dry matter, salt in dry matter, lactic acid and pH were found as 58.69 %. 41,10 %, 42.44 %, 8.36 %, and 4.65 accordingly. The average points ol flavour, texture. appereance, colour and general acceptance were 35.95, 23.91, 11.42. 8,48 respectively and sampled had on average 79.76 point. Of samples 60 % lor coliform bacteria. 66.66 % for yeast and mould and 20 % for moisture and dry matter, 76,70 % for fat in dry matter, 10 % tor salt in dry matter, 36.6 % for pH were lound to be not convenient to White Cheese Standard, It is concluded that a standard manufacturing techniques has not been used for Ihe production of white pickled cheeses consumed in Konya and /or they are not effectively controlled in Ihe production and consumption.